Effect of adding fat to diets during late gestation and lactation - G L Allee; J Salava (Kansas Agricultural Experiment Station Research Reports, 1978)
Recent research at the University of Nebraska suggest that feeding sows high level of fat (15-20%) during late gestation and lactation may increase energy stores in the newborn pig and increase their survival. Adding fat to sows diets increases the fat content of the milk and therefore increases its energy content. The present studies were conducted to evaluate the effect of feeding 6% fat to sows and gilts during late gestation and lactation on pig survival and performance from birth to weaning (14 or 21 days).; Swine Day, Manhattan, KS, November 9, 1978
Keywords: Swine day; 1978; Kansas Agricultural Experiment Station contribution; no. 79-105-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 342; Swine; Fat; Gestation; Lactation; Performance; Survival